Do immediate supervisors underestimate burnout in subordinates? A comparison between burnout self-assessment by nurses and assessment by immediate supervisors - Seršić Darja Maslić; Režić Slađana (Arhiv za Higijenu Rada i Toksikologiju)
The burnout syndrome has been in the focus of occupational health experts for several decades, and a new diagnostic tool – Burnout Assessment Tool (BAT-23) – has given a strong impetus to its research. The tool is designed to self-assess four core dimensions of the burnout syndrome: chronic exhaustion, cognitive and emotional impairment at work, and mental distancing from work. However, little is known about how burnout is assessed from the perspective of a colleague. The aim of our study was to compare the answers to the BAT-23 questionnaire provided by nurses and their immediate supervisors to see if these coincide or differ. Data were collected on a sample of 48 pairs (N=96) of nurses from a clinical hospital in Croatia. Each pair consisted of the head nurse of a particular ward and a randomly selected subordinate nurse in the same ward. BAT-23 was applied in supervisor- and self-assessment versions. Both assessments showed high reliability coefficients (0.73–0.90 for supervisor rating and 0.72–0.86 for self-rating). Cohen’s kappa index of agreement between the two was low (0.059; 62.5 %). As expected, self-assessments indicated high incidence of burnout in nurses, whereas the assessment of their immediate supervisors showed a tendency to underestimate their burnout experience.